# 10.2 Solving quadratic equations by factoring

 Page 1 / 1
This module is from Elementary Algebra</link>by Denny Burzynski and Wade Ellis, Jr. Methods of solving quadratic equations as well as the logic underlying each method are discussed. Factoring, extraction of roots, completing the square, and the quadratic formula are carefully developed. The zero-factor property of real numbers is reintroduced. The chapter also includes graphs of quadratic equations based on the standard parabola, y = x^2, and applied problems from the areas of manufacturing, population, physics, geometry, mathematics (numbers and volumes), and astronomy, which are solved using the five-step method.Objectives of this module: be able to solve quadratic equations by factoring.

## Overview

• Factoring Method
• Solving Mentally After Factoring

## Factoring method

To solve quadratic equations by factoring, we must make use of the zero-factor property.

1. Set the equation equal to zero, that is, get all the nonzero terms on one side of the equal sign and 0 on the other.

$a{x}^{2}+bx+c=0$
2. Factor the quadratic expression.

$\left(\right)\left(\right)=0$
3. By the zero-factor property, at least one of the factors must be zero, so, set each of the factors equal to 0 and solve for the variable.

## Sample set a

Solve the following quadratic equations. (We will show the check for problem 1.)

$\begin{array}{lllllllll}{x}^{2}-7x+12\hfill & =\hfill & 0.\hfill & \hfill & \hfill & \hfill & \hfill & \hfill & \begin{array}{l}\text{The\hspace{0.17em}equation\hspace{0.17em}is\hspace{0.17em}already\hspace{0.17em}}\\ \text{set\hspace{0.17em}equal\hspace{0.17em}to\hspace{0.17em}0}\text{.\hspace{0.17em}Factor}\text{.}\end{array}\hfill \\ \left(x-3\right)\left(x-4\right)\hfill & =\hfill & 0\hfill & \hfill & \hfill & \hfill & \hfill & \hfill & \text{Set\hspace{0.17em}each\hspace{0.17em}factor\hspace{0.17em}equal\hspace{0.17em}to\hspace{0.17em}0}\text{.}\hfill \\ \hfill x-3& =\hfill & 0\hfill & \hfill & \text{or}\hfill & \hfill & x-4\hfill & =\hfill & 0\hfill \\ \hfill x& =\hfill & 3\hfill & \hfill & \text{or}\hfill & \hfill & \hfill x& =\hfill & 4\hfill \end{array}$
$\begin{array}{llllll}Check:\text{\hspace{0.17em}}\text{If}\text{\hspace{0.17em}}x=3,\text{\hspace{0.17em}}{x}^{2}-7x\hfill & +\hfill & 12\hfill & =\hfill & 0\hfill & \hfill \\ \hfill {3}^{2}-7\text{\hspace{0.17em}}·\text{\hspace{0.17em}}3& +\hfill & 12\hfill & =\hfill & 0\hfill & \text{Is\hspace{0.17em}this\hspace{0.17em}correct?}\hfill \\ \hfill 9-21& +\hfill & 12\hfill & =\hfill & 0\hfill & \text{Is\hspace{0.17em}this\hspace{0.17em}correct?}\hfill \\ \hfill & \hfill & 0\hfill & =\hfill & 0\hfill & \text{Yes,\hspace{0.17em}this\hspace{0.17em}is\hspace{0.17em}correct}\text{.}\hfill \end{array}$

$\begin{array}{llllll}Check:\text{\hspace{0.17em}}\text{If}\text{\hspace{0.17em}}x=4,\text{\hspace{0.17em}}{x}^{2}-7x\hfill & +\hfill & 12\hfill & =\hfill & 0\hfill & \hfill \\ \hfill {4}^{2}-7\text{\hspace{0.17em}}·\text{\hspace{0.17em}}4& +\hfill & 12\hfill & =\hfill & 0\hfill & \text{Is\hspace{0.17em}this\hspace{0.17em}correct?}\hfill \\ \hfill 16-28& +\hfill & 12\hfill & =\hfill & 0\hfill & \text{Is\hspace{0.17em}this\hspace{0.17em}correct?}\hfill \\ \hfill & \hfill & 0\hfill & =\hfill & 0\hfill & \text{Yes,\hspace{0.17em}this\hspace{0.17em}is\hspace{0.17em}correct}\text{.}\hfill \end{array}$
Thus, the solutions to this equation are $x=3,\text{\hspace{0.17em}}4.$

$\begin{array}{lllll}\hfill {x}^{2}& =\hfill & 25.\hfill & \hfill & \text{Set\hspace{0.17em}the\hspace{0.17em}equation\hspace{0.17em}equal\hspace{0.17em}to\hspace{0.17em}}0.\hfill \\ \hfill {x}^{2}-25& =\hfill & 0\hfill & \hfill & \text{Factor}\text{.}\hfill \\ \left(x+5\right)\left(x-5\right)\hfill & =\hfill & 0\hfill & \hfill & \text{Set\hspace{0.17em}each\hspace{0.17em}factor\hspace{0.17em}equal\hspace{0.17em}to\hspace{0.17em}}0.\hfill \\ x+5=0\hfill & \text{or}\hfill & \hfill & x-5=0\hfill & \hfill \\ x=-5\hfill & \text{or}\hfill & \hfill & x=5\hfill & \hfill \end{array}$
Thus, the solutions to this equation are $x=5,-5.$

$\begin{array}{lllll}\hfill {x}^{2}& =\hfill & 2x.\hfill & \hfill & \text{Set\hspace{0.17em}the\hspace{0.17em}equation\hspace{0.17em}equal\hspace{0.17em}to\hspace{0.17em}}0.\hfill \\ {x}^{2}-2x\hfill & =\hfill & 0\hfill & \hfill & \text{Factor}\text{.}\hfill \\ x\left(x-2\right)\hfill & \hfill & \hfill & \hfill & \text{Set\hspace{0.17em}each\hspace{0.17em}factor\hspace{0.17em}equal\hspace{0.17em}to\hspace{0.17em}}0.\hfill \\ x=0\hfill & \text{or}\hfill & \hfill & x-2=0\hfill & \hfill \\ \hfill & \hfill & \hfill & x=2\hfill & \hfill \end{array}$
Thus, the solutions to this equation are $x=0,\text{\hspace{0.17em}}2.$

$\begin{array}{lllll}2{x}^{2}+7x-15\hfill & =\hfill & 0.\hfill & \hfill & \text{Factor}\text{.}\hfill \\ \left(2x-3\right)\left(x+5\right)\hfill & =\hfill & 0\hfill & \hfill & \text{Set\hspace{0.17em}each\hspace{0.17em}factor\hspace{0.17em}equal\hspace{0.17em}to\hspace{0.17em}}0.\hfill \\ 2x-3=0\hfill & \text{or}\hfill & \hfill & x+5=0\hfill & \hfill \\ 2x=3\hfill & \text{or}\hfill & \hfill & x=-5\hfill & \hfill \\ x=\frac{3}{2}\hfill & \hfill & \hfill & \hfill & \hfill \end{array}$
Thus, the solutions to this equation are $x=\frac{3}{2},-5.$

$63{x}^{2}=13x+6$
$\begin{array}{lllll}63{x}^{2}-13x-6\hfill & =\hfill & 0\hfill & \hfill & \hfill \\ \left(9x+2\right)\left(7x-3\right)\hfill & =\hfill & 0\hfill & \hfill & \hfill \\ 9x+2=0\hfill & \hfill & \text{or}\hfill & \hfill & 7x-3=0\hfill \\ 9x=-2\hfill & \hfill & \text{or}\hfill & \hfill & 7x=3\hfill \\ x=\frac{-2}{9}\hfill & \hfill & \text{or}\hfill & \hfill & x=\frac{3}{7}\hfill \end{array}$
Thus, the solutions to this equation are $x=\frac{-2}{9},\frac{3}{7}.$

## Practice set a

Solve the following equations, if possible.

$\left(x-7\right)\left(x+4\right)=0$

$x=7,\text{\hspace{0.17em}}-4$

$\left(2x+5\right)\left(5x-7\right)=0$

$x=\frac{-5}{2},\frac{7}{5}$

${x}^{2}+2x-24=0$

$x=4,\text{\hspace{0.17em}}-6$

$6{x}^{2}+13x-5=0$

$x=\frac{1}{3},\frac{-5}{2}$

$5{y}^{2}+2y=3$

$y=\frac{3}{5},-1$

$m\left(2m-11\right)=0$

$m=0,\frac{11}{2}$

$6{p}^{2}=-\left(5p+1\right)$

$p=\frac{-1}{3},\frac{-1}{2}$

${r}^{2}-49=0$

$r=7,-7$

## Solving mentally after factoring

Let’s consider problems 4 and 5 of Sample Set A in more detail. Let’s look particularly at the factorizations $\left(2x-3\right)\left(x+5\right)=0$ and $\left(9x+2\right)\left(7x-3\right)=0.$ The next step is to set each factor equal to zero and solve. We can solve mentally if we understand how to solve linear equations: we transpose the constant from the variable term and then divide by the coefficient of the variable.

## Sample set b

Solve the following equation mentally.

$\left(2x-3\right)\left(x+5\right)=0$
$\begin{array}{lllll}2x-3\hfill & =\hfill & 0\hfill & \hfill & \text{Mentally\hspace{0.17em}add\hspace{0.17em}3\hspace{0.17em}to\hspace{0.17em}both\hspace{0.17em}sides}\text{.\hspace{0.17em}The\hspace{0.17em}constant\hspace{0.17em}changes\hspace{0.17em}sign}\text{.}\hfill \\ \hfill 2x& =\hfill & 3\hfill & \hfill & \begin{array}{l}\text{Divide\hspace{0.17em}by\hspace{0.17em}2,\hspace{0.17em}the\hspace{0.17em}coefficient\hspace{0.17em}of\hspace{0.17em}}x\text{.\hspace{0.17em}The\hspace{0.17em}2\hspace{0.17em}divides\hspace{0.17em}the\hspace{0.17em}constant\hspace{0.17em}3\hspace{0.17em}into\hspace{0.17em}}\frac{3}{2}\text{.\hspace{0.17em}}\\ \text{The\hspace{0.17em}coefficient\hspace{0.17em}becomes\hspace{0.17em}the\hspace{0.17em}denominator}\text{.}\end{array}\hfill \\ \hfill x& =\hfill & \frac{3}{2}\hfill & \hfill & \hfill \\ \hfill x+5& =\hfill & 0\hfill & \hfill & \text{Mentally\hspace{0.17em}subtract\hspace{0.17em}5\hspace{0.17em}from\hspace{0.17em}both\hspace{0.17em}sides}\text{.\hspace{0.17em}The\hspace{0.17em}constant\hspace{0.17em}changes\hspace{0.17em}sign}\text{.}\hfill \\ \hfill x& =\hfill & -5\hfill & \hfill & \text{Divide\hspace{0.17em}by\hspace{0.17em}the\hspace{0.17em}coefficient\hspace{0.17em}of\hspace{0.17em}\hspace{0.17em}}x\text{,\hspace{0.17em}1}\text{.The\hspace{0.17em}coefficient\hspace{0.17em}becomes\hspace{0.17em}the\hspace{0.17em}denominator}\text{.}\hfill \\ \hfill x=\frac{-5}{1}& =\hfill & -5\hfill & \hfill & \hfill \\ \hfill x& =\hfill & -5\hfill & \hfill & \hfill \end{array}$
Now, we can immediately write the solution to the equation after factoring by looking at each factor, changing the sign of the constant, then dividing by the coefficient.

## Practice set b

Solve $\left(9x+2\right)\left(7x-3\right)=0$ using this mental method.

$x=-\frac{2}{9},\frac{3}{7}$

## Exercises

For the following problems, solve the equations, if possible.

$\left(x+1\right)\left(x+3\right)=0$

$x=-1,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-3$

$\left(x+4\right)\left(x+9\right)=0$

$\left(x-5\right)\left(x-1\right)=0$

$x=1,\text{\hspace{0.17em}}\text{\hspace{0.17em}}5$

$\left(x-6\right)\left(x-3\right)=0$

$\left(x-4\right)\left(x+2\right)=0$

$x=-2,\text{\hspace{0.17em}}\text{\hspace{0.17em}}4$

$\left(x+6\right)\left(x-1\right)=0$

$\left(2x+1\right)\left(x-7\right)=0$

$x=-\frac{1}{2},\text{\hspace{0.17em}}\text{\hspace{0.17em}}7$

$\left(3x+2\right)\left(x-1\right)=0$

$\left(4x+3\right)\left(3x-2\right)=0$

$x=-\frac{3}{4},\text{\hspace{0.17em}}\text{\hspace{0.17em}}\frac{2}{3}$

$\left(5x-1\right)\left(4x+7\right)=0$

$\left(6x+5\right)\left(9x-4\right)=0$

$x=-\frac{5}{6},\text{\hspace{0.17em}}\text{\hspace{0.17em}}\frac{4}{9}$

$\left(3a+1\right)\left(3a-1\right)=0$

$x\left(x+4\right)=0$

$x=-4,\text{\hspace{0.17em}}\text{\hspace{0.17em}}0$

$y\left(y-5\right)=0$

$y\left(3y-4\right)=0$

$y=0,\text{\hspace{0.17em}}\text{\hspace{0.17em}}\text{\hspace{0.17em}}\frac{4}{3}$

$b\left(4b+5\right)=0$

$x\left(2x+1\right)\left(2x+8\right)=0$

$x=-4,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-\text{\hspace{0.17em}}\frac{1}{2},\text{\hspace{0.17em}}\text{\hspace{0.17em}}0$

$y\left(5y+2\right)\left(2y-1\right)=0$

${\left(x-8\right)}^{2}=0$

$x=8$

${\left(x-2\right)}^{2}=0$

${\left(b+7\right)}^{2}=0$

$b=-7$

${\left(a+1\right)}^{2}=0$

$x{\left(x-4\right)}^{2}=0$

$x=0,\text{\hspace{0.17em}}\text{\hspace{0.17em}}4$

$y{\left(y+9\right)}^{2}=0$

$y{\left(y-7\right)}^{2}=0$

$y=0,\text{\hspace{0.17em}}\text{\hspace{0.17em}}7$

$y{\left(y+5\right)}^{2}=0$

${x}^{2}-4=0$

$x=-2,\text{\hspace{0.17em}}\text{\hspace{0.17em}}2$

${x}^{2}+9=0$

${x}^{2}+36=0$

no solution

${x}^{2}-25=0$

${a}^{2}-100=0$

$a=-10,\text{\hspace{0.17em}}\text{\hspace{0.17em}}10$

${a}^{2}-81=0$

${b}^{2}-49=0$

$b=7,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-7$

${y}^{2}-1=0$

$3{a}^{2}-75=0$

$a=5,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-5$

$5{b}^{2}-20=0$

${y}^{3}-y=0$

$y=0,\text{\hspace{0.17em}}\text{\hspace{0.17em}}1,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-1$

${a}^{2}=9$

${b}^{2}=4$

$b=2,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-2$

${b}^{2}=1$

${a}^{2}=36$

$a=6,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-6$

$3{a}^{2}=12$

$-2{x}^{2}=-4$

$x=\sqrt{2},\text{\hspace{0.17em}}\text{\hspace{0.17em}}-\sqrt{2}$

$-2{a}^{2}=-50$

$-7{b}^{2}=-63$

$b=3,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-3$

$-2{x}^{2}=-32$

$3{b}^{2}=48$

$b=4,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-4$

${a}^{2}-8a+16=0$

${y}^{2}+10y+25=0$

$y=-5$

${y}^{2}+9y+16=0$

${x}^{2}-2x-1=0$

no solution

${a}^{2}+6a+9=0$

${a}^{2}+4a+4=0$

$a=-2$

${x}^{2}+12x=-36$

${b}^{2}-14b=-49$

$b=7$

$3{a}^{2}+18a+27=0$

$2{m}^{3}+4{m}^{2}+2m=0$

$m=0,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-1$

$3m{n}^{2}-36mn+36m=0$

${a}^{2}+2a-3=0$

$a=-3,\text{\hspace{0.17em}}\text{\hspace{0.17em}}1$

${a}^{2}+3a-10=0$

${x}^{2}+9x+14=0$

$x=-7,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-2$

${x}^{2}-7x+12=3$

${b}^{2}+12b+27=0$

$b=-9,\text{\hspace{0.17em}}\text{\hspace{0.17em}}-3$

${b}^{2}-3b+2=0$

${x}^{2}-13x=-42$

$x=6,\text{\hspace{0.17em}}\text{\hspace{0.17em}}7$

${a}^{3}=-8{a}^{2}-15a$

$6{a}^{2}+13a+5=0$

$a=-\frac{5}{3},\text{\hspace{0.17em}}\text{\hspace{0.17em}}-\frac{1}{2}$

$6{x}^{2}-4x-2=0$

$12{a}^{2}+15a+3=0$

$a=-\frac{1}{4},\text{\hspace{0.17em}}\text{\hspace{0.17em}}-1$

$18{b}^{2}+24b+6=0$

$12{a}^{2}+24a+12=0$

$a=-1$

$4{x}^{2}-4x=-1$

$2{x}^{2}=x+15$

$x=-\frac{5}{2},\text{\hspace{0.17em}}\text{\hspace{0.17em}}3$

$4{a}^{2}=4a+3$

$4{y}^{2}=-4y-2$

no solution

$9{y}^{2}=9y+18$

## Exercises for review

( [link] ) Simplify ${\left({x}^{4}{y}^{3}\right)}^{2}{\left(x{y}^{2}\right)}^{4}.$

${x}^{12}{y}^{14}$

( [link] ) Write ${\left({x}^{-2}{y}^{3}{w}^{4}\right)}^{-2}$ so that only positive exponents appear.

( [link] ) Find the sum: $\frac{x}{{x}^{2}-x-2}+\frac{1}{{x}^{2}-3x+2}.$

$\frac{{x}^{2}+1}{\left(x+1\right)\left(x-1\right)\left(x-2\right)}$

( [link] ) Simplify $\frac{\frac{1}{a}+\frac{1}{b}}{\frac{1}{a}-\frac{1}{b}}.$

( [link] ) Solve $\left(x+4\right)\left(3x+1\right)=0.$

$x=-4,\text{\hspace{0.17em}}\text{\hspace{0.17em}}\frac{-1}{3}$

#### Questions & Answers

what is microeconomics and macroeconomics
microeconomic deal with the study of individual firms and household and macroeconomics deal with the economy as a whole.
Ebenezer
definition of Monopoly
Wat is the importance of economics
it broaden one's mind
malonzy
it help us to make good choices
Yussif
what is an efficient wage and how it causes structural unemployment and how it could be shown graphically?
economics is a social science and an art discuss
further explanation on the definition
is demand the same as quantity demanded
Samuel
what is business economics
business economics is the way the society uses its limited resources to satisfy their unlimited wants
Sekai
what is business economics
how did Mc connel defined economics
what is a economy planning?
what is demand
demand means desire for a commodity backed by willingness & ability to pay for that commodity
Rajesh
what is supply
Akoheni
supply means suppliers supplying more commodities when price's high or less when price's low to satisfy human want
Prince
the coefficient of price elasticity of supply is the measure of percentage change in the quantity supplied of a good due to a given percentage change in its price.
Khushiba
Please what is Economics of Scales?
Prince
what is cardinal and ordinal utility?
Khushiba
Cardinal utility is the satisfaction derived by the consumers from the consumption of goods and services while ordinal is ranked in terms of preference.
Grace
👍
Khushiba
Please explain what is meant by Economic Integration?
Prince
Please I need help!!!!
Prince
economics scales I don't know but I know laws of returns to scale
Khushiba
hello
TIMAH
hello
Khushiba
can someone help explain to me what is fairly inelastic dd
TIMAH
Economics Economics - The study of how people use their limited resources to try to satisfy unlimited wants
Abdullah
Economic integration has been one of the main economic developments affecting international trade in the last years. Countries have wanted to engage in economic cooperation to use their respective resources more effectively and to provide large markets for member-countries of the resulting integrate
Abdullah
Inelastic Demand When consumers are relatively unresponsive to price changes. A PED coefficient of less than one means that a particular change in the price of a good will be met by a proportionally smaller change in the quantity demanded.
Abdullah
demand refers to goods and services that a consumer is willing and able to buy at given rate over a given period of time
Freeman
Demand  - The entire relationship between the quantity of product that buyers wish to purchase per period time and the price of that product..
Abdullah
what are the factor that affect demand
akbal
what is development planning?
What is economics?
economics is study of scarcity and how humans make decisions.
reason for development planning in West Africa
Emmanuel
what is development planning?
Emmanuel
What is homo Economicus?
when a person is part 50% rational and the other part of him is 50% focused on money as an incentive
Yahir
what makes the economy to be stable
what measures are necessary to the economy which is not doing fine
BELDON
must find out the problems originating from and take remedy for it.
Rigved
Economics as a social science Discuss
Sire
in a comparison of the stages of meiosis to the stage of mitosis, which stages are unique to meiosis and which stages have the same event in botg meiosis and mitosis
Please keep in mind that it's not allowed to promote any social groups (whatsapp, facebook, etc...), exchange phone numbers, email addresses or ask for personal information on QuizOver's platform. By By By   By By  By Lakeima Roberts   